Using long-term tree diversity experiments to explore the mechanisms of temporal shifts in forest ecosystem functioning - Koricheva, Julia; Barton, Kasey E.; Felix, Juri A.; Cooper, Amanda; Jensen, Joel; Jucker, Tommaso; Ruohomäki, Kai (WILEY, 2025)
Plant diversity is known to influence ecosystem functioning, but the strength and direction of this relationship vary considerably among studies, most of which have a short duration. In communities with long-lived species, such as forests, traits of individual trees change from seedlings to maturity, and the environment in which trees grow also continually changes through stand development and forest succession. We argue that interactions between these individual and community-level effects over time will alter biodiversity-ecosystem functioning (BEF) relationships, likely explaining at least part of the reported variation in BEF effects among studies. We outline a series of mechanisms through which temporal changes at the tree and stand levels can alter BEF relationships and illustrate these processes using data from the long-term Satakunta forest diversity experiments in Finland. We argue that long-term forest diversity experiments are essential to robustly characterize temporal dynamics emerging from the complex interplay between plant functional traits and environmental conditions over time. These experiments can provide critical insights for predicting the consequences of biodiversity loss on ecosystem functioning and service provisioning over time.